PENINGKATAN KEMAMPUAN GURU DALAM MELAKSANAKAN PERBAIKAN PEMBELAJARAN MELALUI PENELITIAN TINDAKAN KELAS (PTK) SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN SISWAPADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DENGAN PEMBELAJARAN SISWA AKTIF (CHILDREN ACTIVE LEARNING) D - MUSNIATI MUSNIATI (JURNAL ILMIAH SIMANTEK, 2023)
The ability of teachers to plan, implement, evaluate and follow up on a learning process that must be carried out by teachers, The ability of teachers to carry out learning improvements through classroom action research (PTK) Classroom research, through Classroom Action Research (PTK) carried out by teachers is an activity of researchers as well as the principal in carrying out school action research that means conducting PTS in teacher activities to carry out PTK as an effort Increase Student Understanding of Natural Science Subjects with Children Active Learning. This research is a School Action Research (PTS) conducted at SD Negeri 19 Batang Gasan. PTS is carried out in the process of an activity through 2 cycles. The effectiveness of actions in each cycle is measured from the results of observations and results that have been improved to students so that the completeness of learning can be measured by teachers who are used as models in the school, which is reflected in learning activities ranging from planning, presenting subject matter in line with facilitating student understanding in receiving a lesson, analyzed by student understanding of the subject matter of the Reproduction Process in living things in class VI The first semester of SD Negeri 34 Batang Gasan, Padang Pariaman Regency has proven to increase. Of the 25 students, 21 students have been able to achieve completion scores. The class average reached 77.6.